Prevalence of fundus tessellation and its associated factors in Chinese children and adolescents with high myopia. Issue 8 (24th February 2021) - Cheng, Tianyu; Deng, Junjie; Xu, Xian; Zhang, Bo; Wang, Jingjing; Xiong, Shuyu; Du, Yuchen; Yu, Suqin; Gong, Wei; Zhao, Huijuan; Luan, Mengli; Fan, Ying; et al.
Abstract: Purpose: To investigate the prevalence and associated factors of fundus tessellation in highly myopic children and adolescents. Methods: A total of 513 high myopes (spherical equivalent [SE] ≤ −5.0 D, 4–19 years of age) without any advanced pathological myopic lesions were enrolled. Fundus photographs and choroidal thickness (ChT) data were collected by SS‐OCT. A novel grading approach was adopted to classify fundus tessellation into four categories on colour fundus photography, referring to the location of tessellation divided by an Early Treatment Diabetic Retinopathy Study grid centred on the fovea, through which closer to the fovea represents higher grades of fundus tessellation. Peripapillary atrophy (PPA) area and ovality index were also measured. Results: Among the participants, with a mean age of 13.47 ± 3.13 years and mean SE of − 8.34 ± 1.91 D, there were 29 (5.7%), 95 (18.5%), 233 (45.4%) and 156 (30.4%) participants with grade 0 to grade 3 fundus tessellation, respectively. The ChT in both the macular and peripapillary area was negatively correlated with the fundus tessellation grade ( R  = −0.763 and −0.537, respectively, all p < 0.001). Higher grades of fundus tessellation were independently associated with thinner macular ChT (OR = 1.734, 95% CI: 1.621–1.856, p < 0.001), longer axial length (OR = 1.368, 95% CI: 1.105–1.695, p = 0.004), larger PPA area (OR = 1.391, 95% CI: 1.073–1.802, p = 0.013) and the female sex (OR = 1.605, 95% CI: 1.092–2.359, p = 0.016). Conclusion: The fundus tessellation grade could reflect the ChT, representing the severity of myopic maculopathy among young high myopes who rarely had any advanced lesions of pathological myopia. Fundus tessellation grade might be a potential index for assessing early‐stage myopic maculopathy in children and adolescents.